(untitled) (Security Dialogues, 2023)
The current study examines the effects of one of the modern crises nowadays, andthat is the terrorism. Today’s terrorist threats have changed, and terrorist groups are now more geographically dispersed and their tactics more diversified. To address this evolving terrorist threat across the globe and within the homeland, our approach to counterterrorism must evolve. The preparation for a terrorist attack, a rampage, hostage taking or other violentattacks is an essential part of crisis management these days. Rapid, careful intervention isoften vital in situation of terrorism and other external threats. Time is a very decisive factorin exceptional and critical situations. Accordingly, an essential prerequisite to ensuring thatour formidable resources are focused where they can have the most effect is a sober andempirical understanding of the threat coupled with a clear, comprehensive, and coherentstrategy. Without such a strategy, we risk embracing policies and pushing solutions thatmay not only be dated, but may have become irrelevant. We also lose sight of current andprojected trends and patterns and thereby risk preparing to counter and respond to possibly illusory threats and challenges.